The effect of storage condition on physicochemical properties of some stingless bee honey collected in Malaysia local market - Wan Nadja, Julika; Azilah, Ajit; Aishath, Naila; Ahmad Ziad, Sulaiman (Elsevier Ltd, 2022)
It is essential to know the behavior of Malaysian stingless bee honey in different storage conditions so that the characteristics of the honey can be preserved and to ensure the product is safe to consume. Therefore, this study aims to investigate the influence of storage conditions (materials, temperature and time) as well as the correlation between pH, HMF and storage parameters on stingless bee honey quality. To conduct this study, all honey samples were stored in ambient and 4 °C conditions for 90 days. Physicochemical analyses such as pH, free acidity, moisture content, HMF and diastase activity were analysed by adapting the Malaysian kelulut standard, AOAC methods and Harmonized Methods of the International Honey Commission. The results showed that containers (glass and plastic) only have a minor influence on most honey samples physicochemical properties. Besides that, HMF showed an increasing trend with increasing time and temperature storage while pH decreased with increasing time storage. It was also determined that honey stored at room temperature (25 °C) deteriorates faster than honey stored at 4 °C. In conclusion, it was recommended to keep honey at cold temperature (4°) in a glass container and consume the honey in 90 days after harvesting or purchasing to preserve honey quality.